Determination of Aflatoxin M1 level in raw milk of East Mazandaran retails (Short Comunication) - l. Golestan; kh. rahimi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2019)
Mycotoxin contamination of foodstuff and its transmission to consumers are extremely important from the public health point of view. Aflatoxin M1 (AFM1) is a hepatocarcinogenic toxin found in the milk of animals that have consumed feeds contaminated with aflatoxin B1. The aim of this study was to determine the level of AFM1 in raw milk at traditional dairy retails of the east of Mazandaran province. A total of 80 cow raw milk samples was randomly collected from retails of 10 cities of Mazandaran during March 2015. The level of AFM1 was measured by ELISA assay using commercial kits and a microplate reader. All raw milk samples contained measurable amounts of AFM1. The results showed that 6.25% of the total samples had higher concentrations permitted by the Institute of Standards and Industrial Research of Iran; moreover, 17.5% of the samples were contaminated with higher concentrations of AFM1 than the maximum allowed limit set by the European Commission. Results revealed any significant relationship in the AFM1 concentrations between the sampling cities. According to the outcomes, it can be concluded that adequate control measures at the farm level may have resulted in reduced concentrations of AFM1 in raw milk of Mazandaran province; however, frequent monitoring is crucial.